The math chef : over 60 math activities and recipes for kids - D'Amico, Joan, 1957-; Drummond, Karen Eich.; Cash-Walsh, Tina, 1960- (New York : J. Wiley, 1997)
Relates math and cookery by presenting math concepts and reinforcing them with recipes. Provides practice in converting from English to metric system, multiplying quantities, measuring area, estimating, and more.
Discovering the kitchen -- Measuring. How many grams is a pound of potatoes? -- How many quarts is a liter of milk? -- How long is that giant cookie? -- How much soup is in a bowl of soup? -- What does a handful of pasta weigh? -- How do you cook candy? -- Arithmetic. How do you triple a sandwich recipe? -- How to you cut an applesauce recipe in half? -- How much lettuce do you need for 6 salads? -- Fractions and percents. What's 1/3 of a waffle? -- What's the percent of margarine in a muffin? -- Geometry. What's the area of a brownie? -- What's the diameter of a cupcake? -- What's the circumference of a pie? -- Appendix A. Answers to the math activities -- Appendix B. Nutrient content of recipes -- Appendix C. Nutrition in a nutshell -- Appendix D. What's safe to eat? -- Glossary.
Includes index.
Keywords: Cooking -- Juvenile literature; Mathematics -- Juvenile literature